Comissão 3.4 - poluição, remediação do solo e recuperação de áreas degradadas - Pereira, Bruno Fernando Faria; Rozane, Danilo Eduardo [UNESP]; Araújo, Suzana Romeiro; Barth, Gabriel; Queiroz, Rafaela Josemara Barbosa [UNESP]; Nogueira, Thiago Assis Rodrigues; Moraes, Milton Ferreira; Cabral, Cleusa Pereira; Boaretto, Antonio Enedi; Malavolta, Eurípedes (FapUNIFESP (SciELO), 2011)
Among the toxic elements, Cd has received considerable attention in view of its association with a number of human health problems. The objectives of this study were to evaluate the Cd availability and accumulation in soil, transfer rate and toxicity in lettuce and rice plants grown in a Cd-contaminated Typic Hapludox. Two simultaneous greenhouse experiments with lettuce and rice test plants were conducted in a randomized complete block design with four replications. The treatments consisted of four Cd rates (CdCl2), 0.0; 1.3; 3.0 and 6.0 mg kg-1, based on the guidelines recommended by the Environmental Agency of the State of São Paulo, Brazil (Cetesb). Higher Cd rates increased extractable Cd (using Mehlich-3, Mehlich-1 and DTPA chemical extractants) and decreased lettuce and rice dry matter yields. However, no visual toxicity symptoms were observed in plants. Mehlich-1, Mehlich-3 and DTPA extractants were effective in predicting soil Cd availability as well as the Cd concentration and accumulation in plant parts. Cadmium concentration in rice remained below the threshold for human consumption established by Brazilian legislation. On the other hand, lettuce Cd Concentration in edible parts exceeded the acceptable limit.
Cadmium availability and accumulation by lettuce and rice
Keywords: Chemical extractants; Heavy metals; Human health; Lactuca sativa L; Oryza sativa L; Soil pollution